Pengaruh Faktor Fundamental Dan Economic Value Added (Eva) Terhadap Return Saham - Andi Usmar (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to determine the fundamental factors and economic value added to stock returns. The data is obtained from ICMD and the issuer's annual financial statements for the 2016-2020 period. The total population of this study was 45 companies and the number of samples was 17 companies by passing the purposive sampling stage. The analysis technique that will be used in this study is multiple linear regression panel data, to obtain a comprehensive picture. Regarding the relationship between one variable with another variable. The results showed that there was an increase in stock returns in companies that were included in the research list with the assumption that the return on assets, price earning ratio, debt to equity ratio, net profit margin, earnings per share and economic value added variables did not change. The ROA, PER, NPM, EPS and EVA variables have a significant positive effect on stock returns, while the DER variable has a significant negative effect on stock returns in companies listed in LQ 45 on the IDX.